Implementasi Kurikulum Cinta Dalam Pembelajaran Pendidikan Agama Islam Untuk Membentuk Karakter Moderasi Beragama Di Sekolah Umum - Nurhilaliyah (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
This study aims to conduct an in-depth exploration of a love-based curriculum in Islamic Religious Education learning at public school in order to shape a character of religious moderation. Religious moderation itself is a religious approach that emphasizes a balanced attitude, tolerance, and respect for differences, highlighting that in the educational world, approach is an important aspect for forming students' characters who are wholly peace-loving. Therefore, this curriculum is designed to instill the value of love for God, fellow human beings, the environment, and the nation from an early age. There are four main aspects in this curriculum, one of which is fostering love for God (Hablum Minallah). The Ministry of Religious Affairs, through the Directorate General of Islamic Education, has prepared a guidebook that will serve as a reference for educators in incorporating values of love, tolerance, and spirituality into learning. The method used in this study was a literature review on educational policies, religious writings, and academic research to analyze how the Love Curriculum can shape the character of religious moderation. The results of the study show that a love-based curriculum successfully shapes students' character to better appreciate differences and encourage mutual respect.